Exploring English for medical purposes (EMP) teacher cognition in the Chinese context - Cao, Zhongkai; Zhang, Zaihong; Liu, Ya; Pu, Liping (Frontiers in Psychology, 2022)
Abstract: It has been a growing trend in Chinese universities to shift from English for general purposes (EGP) to English for specific purposes (ESP) teaching. Against this background, large groups of teachers previously engaged in teaching EGP have become or are becoming ESP teachers, which means a complex process of learning for subject-specific information, transforming teaching practices and constructing new identities. Despite this, very little has been written about the ESP teacher cognition of language teaching or the factors influencing this shift in teaching. This study involved English for Medical Purposes (EMP) teachers in Chinese universities as participants, and a scale of EMP teacher cognition with 31 items was developed on the basis of questionnaire results. Data from exploratory factor analysis revealed six dimensions of the scale, namely, teacher attitude, teacher belief, teacher learning, teacher support, role identification, and teacher practice—that combine to constitute and influence EMP teacher cognition. While the identity factor has attracted wide attention in ESP teacher research, other factors have largely been neglected. Thus, this research highlights the importance of more factors in shaping and changing the language teaching cognition of EMP or ESP teachers in large, especially the teacher belief factor. In addition, results of independent samples t-tests indicated significant difference in EMP teacher learning in terms of gender, differences in EMP teacher attitude and teacher support in terms of EMP teaching experience. Suggestions for enhancing EMP teacher cognition are offered on the basis of the conclusions of this research.